1989
DOI: 10.1159/000199900
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effects of Cimetropium Bromide and Atropine on Human Esophageal Motor Functions

Abstract: The effects of atropine and cimetropium bromide, a new antimuscarinic compound with strong spasmolytic properties, were studied on human esophageal motility. Twenty healthy subjects underwent esophageal manometry with continuous monitoring of lower esophageal sphincter pressure (LESP), and of amplitude, duration and velocity of contractions of the esophageal body. After a 30-min basal period, atropine (12 µg/kg) or cimetropium (5 mg) were administered as an intravenous bolus in a cross-over random manner and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The observed decrease in the contraction amplitude of primary peristalsis or even an abolished peristalsis after TC and BIP is in line with the reported effects of other anticholinergic drugs such as atropine, scopolamine, hyoscyamine, cimetropium bromide and propantheline bromide 1 –6 . TC, which cannot pass the blood–brain barrier due to its quaternary ammonium structure, 13 exerts its effect by blockade of the oesophageal muscarinergic M3 receptors of the smooth muscle, 16 while the site of action is unknown for BIP.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The observed decrease in the contraction amplitude of primary peristalsis or even an abolished peristalsis after TC and BIP is in line with the reported effects of other anticholinergic drugs such as atropine, scopolamine, hyoscyamine, cimetropium bromide and propantheline bromide 1 –6 . TC, which cannot pass the blood–brain barrier due to its quaternary ammonium structure, 13 exerts its effect by blockade of the oesophageal muscarinergic M3 receptors of the smooth muscle, 16 while the site of action is unknown for BIP.…”
Section: Discussionsupporting
confidence: 83%
“…A shortened duration was found after anticholinergic drugs in two studies, 1 , 6 while, in accordance with our study, no effect was observed by others 3 , . 4 The reason might be that it is difficult to measure correctly the duration of contractions with a very low amplitude. A more accurate measurement should be possible with a strain gauge electronic pressure device such as that used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cimetropium bromide (5 mg; i.v.) as a non‐selective antimuscarinic receptor antagonist reduced the amplitude of the esophageal contractions and the LESP to a similar extent and with fewer side‐effects, but with less duration than atropine (12 μ g/kg) in healthy volunteers 15 . Furthermore, cimetropium bromide (10 mg; i.v.)…”
Section: Pharmacology Of the Esophagusmentioning
confidence: 95%
“…Cimetropium has been evaluated as a new anticholinergic agent for its effect on esophageal motility. Cimetropium bromide (5 mg) as a nonselective antimuscarinic receptor antagonist reduced the amplitude of esophageal contractions and the LESP to a similar extent but with less duration than atropine (12 Ixg/kg) [7].…”
Section: Cholinergic and Anticholinergic Agentsmentioning
confidence: 96%